Paracrine Fibroblast Growth Factor 1 Functions as Potent Therapeutic Agent for Intrahepatic Cholestasis by Downregulating Synthesis of Bile Acid - Lin, Huan; Zhou, Chuanren; Hou, Yushu; Li, Qi; Qiao, Guanting; Wang, Yang; Huang, Zhifeng; Niu, Jianlou (Frontiers in Pharmacology, 2019)
Endocrine fibroblast growth factor (FGF) 19 has been shown to be capable of maintaining bile acid (BA) homeostasis and thus hold promise to be a potential therapeutic agent for cholestasis liver disease. However, whether paracrine FGFs possess this BA regulatory activity remains to be determined. In our study, we identified that paracrine fibroblast growth factor 1 (FGF1) was selectively down-regulated in the liver of alpha naphthylisothiocyanate (ANIT) -induced intrahepatic cholestasis mice, suggesting a pathological relevance of this paracrine FGF with abnormal BA metabolism. Therefore, we evaluated the effects of engineered FGF1 mutant -FGF1 ΔHBS on the metabolism of hepatic BA and found that this protein showed a more potent inhibitory effect of BA biosynthesis than FGF19 without any hepatic mitogenic activity. Moreover, the chronic administration of FGF1 ΔHBS protected liver against ANIT-induced injury by reducing hepatic BA accumulation. Taken together, these data suggest that FGF1 ΔHBS may function as a potent therapeutic agent for intrahepatic cholestasis liver disease.